Digital Marketing Trends and Innovations in Indonesia: A Qualitative Exploration of Emerging Practices - Erlangga, Heri; Riani, Dini; Hindarsah, Ida; Setiawati, Tita; Riadi, Farid (Jurnal Office, 2023)
This research explores trends and innovations in digital marketing in Indonesia through a qualitative approach. Along with the rapid development of technology and increasing use of the internet, the marketing landscape in Indonesia has experienced significant changes. This study aims to identify emerging new practices and understand how companies in Indonesia are adopting the latest digital marketing strategies. Through in-depth interviews with digital marketing experts and practitioners, this research reveals various innovative approaches used to increase customer engagement and optimize business performance. The findings show that the use of social media, interactive content, and data analytics are key in today's digital marketing strategies. In addition, personalization and enhanced customer experience are the main focus to win market competition. This study also highlights the challenges companies face in implementing digital strategies, such as limited resources and the need for rapid adaptation to technological changes. By understanding these trends and innovations, companies can develop more effective strategies to achieve competitive advantage in the Indonesian digital market.